Protest song Masters of War Boba Dylana – analiza luhmannowska - Ostrowski, Marek (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2019)
Artykuł interpretuje protest song Boba Dylana Masters of War z perspektywy teorii systemów.